Peritoneal borderline cystoadenocarcinoma - Girão, Manoel João Batista Castello; Sartori, Marair Gracio Ferreira; Gonçalves, Wagner José; Lima, Geraldo Rodrigues de (São Paulo Medical Journal, 1998)
Carcinomas of peritoneal origin represent a seldom diagnosed entity of unknown etiology, with important implications in terms of prophylactic oophorectomy. Initially described in patients belonging to families at high risk for ovarian cancer, it possibly has a pathogeny similar to that of endosalpingiosis and of some cases of endometriosis. We report a case of peritoneal borderline mucinous carcinoma with an anatomopathological diagnosis of normal ovaries.